Anti-Bisexual Discrimination, Hazardous Alcohol Use, and Sexual Victimization Among Bi+ Individuals - (:unkn) unknown (My University, 2022)
Bi+ individuals are at an elevated risk of sexual victimization compared to other sexual minorities. Hazardous alcohol use and minority stress are two factors proposed to contribute to increased rates of sexual victimization among bi+ individuals. The present study investigated the roles of distal and proximal minority stress, general life stress, negative affect, and hazardous alcohol use as predictors of sexual victimization in a sample of 192 bi+ young adults. Results indicated that experiences of anti-bisexual discrimination were associated with an increased likelihood of experiencing past year rape victimization. A direct, positive association between hazardous alcohol use and past year rape victimization, as well as an indirect effect of anti-bisexual discrimination on past year rape victimization through increases in hazardous alcohol use, was also found. Results from the present study expand our understanding of predictors of sexual victimization among bi+ individuals and support the notion that a shift to focus on distal minority stressors may be more effective in reducing sexual victimization than targeting proximal minority stressors.